(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
Dental caries remains a prevalent issue worldwide, affecting individuals of all ages. This article discusses the treatment methods for both acute and chronic carious lesions, emphasizing modern therapeutic approaches. Additionally, it explores preventive measures and prescription-based interventions to mitigate the risk of caries progression. The article also highlights the importance of early diagnosis and patient education in preventing dental decay.